Association of OPRD1 polymorphisms with heroin dependence in a large case‐control series. (13th April 2012) - Nelson, Elliot C.; Lynskey, Michael T.; Heath, Andrew C.; Wray, Naomi; Agrawal, Arpana; Shand, Fiona L.; Henders, Anjali K.; Wallace, Leanne; Todorov, Alexandre A.; Schrage, Andrew J.; Madden, Pamela A. F.; Degenhardt, Louisa; et al.
ABSTRACT Genes encoding the opioid receptors (OPRM1, OPRD1 and OPRK1) are obvious candidates for involvement in risk for heroin dependence. Prior association studies commonly had samples of modest size, included limited single nucleotide polymorphism (SNP) coverage of these genes and yielded inconsistent results. Participants for the current investigation included 1459 heroin‐dependent cases ascertained from maintenance clinics in New South Wales, Australia, 1495 unrelated individuals selected from an Australian sample of twins and siblings as not meeting DSM‐IV criteria for lifetime alcohol or illicit drug dependence (non‐dependent controls) and 531 controls ascertained from economically disadvantaged neighborhoods in proximity to the maintenance clinics. A total of 136 OPRM1, OPRD1 and OPRK1 SNPs were genotyped in this sample. After controlling for admixture with principal components analysis, our comparison of cases to non‐dependent controls found four OPRD1 SNPs in fairly high linkage disequilibrium for which adjusted P values remained significant (e.g. rs2236857; OR 1.25; P = 2.95 × 10−4) replicating a previously reported association. A post hoc analysis revealed that the two SNP (rs2236857 and rs581111) GA haplotype in OPRD1 is associated with greater risk (OR 1.68; P = 1.41 × 10−5). No OPRM1 or OPRK1 SNPs reached more than nominal significance. Comparisons of cases to neighborhood controls reached only nominal significance. Our results replicate a prior report providing strong evidence implicating OPRD1 SNPs and, in particular, the two SNP (rs2236857 and rs581111) GA haplotype in liability for heroin dependence. Support was not found for similar association involving either OPRM1 or OPRK1 SNPs.